DISASTER RESPONSE MOSQUE: A MOSQUE AS A CENTER FOR THE RESCUE OF THE UMMAH - Yudhi Gunardi; M Syaom Barliana (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2021)
AbstractDisaster events are almost impossible to predict accurately when, where and how big so that the preparedness of all elements of society in various regions is a basic need so that the impact of disaster risk can be minimized. The number of mosques in various parts of Indonesia, both institutionally and physically, is a strategic means as a center for saving people from disasters, so that they become interesting objects for research. This study aims to describe the strategic role of planning and designing mosques to reduce disaster risk. The results of this study indicate that planning and designing mosques to reduce disaster risk can be carried out through three stages as follows: (1) Pre-disaster stage through planning: mitigation programs (non-physical), infrastructure planning (physical), site selection, building planning and environment. (2) In the emergency response stage, the design of the mosque must be adaptive to readiness as an information post, volunteers and logistics, medical service facilities, refugee shelter facilities, refugee sanitation facilities, public kitchen facilities, and trauma healing facilities. (3) Post-disaster stage through metal/trauma healing rehabilitation, community economic empowerment program, evaluation, and capacity building to deal with disasters. Keywords: Disaster, Mitigation, Disaster Management, Disaster Response Mosque.